Intertypic cross-reactions of nonneutralizing, monoclonal poliovirus antibodies. - Vrijsen, R (1984)
Quantitative data are presented on (i) the intertypic cross-reactions of polyclonal, guinea pig antibodies directed against the N or H antigen of type 1 poliovirus and (ii) a set of five nonneutralizing, mouse hybridoma antibodies raised against N antigen or a mixture of capsid polypeptides VP1, VP2, and VP3. Three of these antibodies recognize H antigen and VP1, the fourth H antigen only, and the fifth VP3 only. The antibodies recognize either only homotypic antigens or the antigens of the three serotypes.